ALTERAÇÕES HISTOLÓGICAS CAUSADAS POR NANOTUBOS DE CARBONO DE PAREDES MÚLTIPLAS EM CAMUNDONGOS - Martins, Nára Maria Beck (2011)
Carbon nanotubes (CNT) belong to a new group of materials which have special properties and have been the focus of many studies in the biomedical area. Researches on toxicity are important to evaluate the possibility of using them in organic beings. In that context, we analyzed the histological changes of multi-walled carbon nanotubes (MWCNT) in mice, after oral exposure. To this end, female mice were orally exposed to 100 μL of MWCNT/day, suspended in a PBS/Tween 80® solution, at a concentration of 5 mg/mL, for 7 days. A group of mice was sacrificed on the 7th day and another on the 30th day. Liver, spleen, heart, lungs, kidneys and brain were collected and fixed in formaldehyde 10% for histological analysis (v/v). MWCNT accumulation in the organs was detected, deeper in mice from the second group. Inflammation in the liver was also observed in mice that were sacrificed on the 30th day. These inflammatory disturbances can be related to the direct action of MWCNT in organism. The data analysis suggests that oral exposure to a 0,5 mg/day dose of MWCNT causes accumulation of the material in organs and time-dependent hepatic inflammatory signals